Problems in clinical communication problems involving hospitalised patients - Surmacka, Joanna; Motyka, Marek (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Introduction. Assuming the role of a patient and dealing with the realities of hospitalisation is stressful, especially when unexpected. Stress mitigation requires special attention on part of doctors and nurses. Given the numerous sources of frustration and stress related to illness and hospitalisation, as well as their connection to healthcare quality, we decided to study the most common types of clinical communication problems, as indicated by patients. Aim of the study. To define the most common problems in clinical communication between patients and medical personnel. Material and methods. The analysis was based on 50 letters to the editor of one of the popular yournals, which asked its readers to share their hospital experiences. The applied method was diagnostic document analysis. Results. The vast majority of problems concerned broadly understood communication with the staff. Most respondents mentioned traumatic experiences connected to receiving information from the hospital’s personnel (80%), described staff acting instrumentally without even trying to establish a therapeutic relationship (50%), had their fears and anxieties ignored or belittled (36%) and felt that their intimacy was not respected during physical examinations or hygiene procedures (28%). Conclusions. Therapeutic communication with the patient is still extremely rare in hospitals, becoming an aspiration rather than an actual component of care.